Distributed formation tracking of networked mobile robots under unknown slippage effects. (April 2015) - Yoo, Sung Jin; Kim, Tae-Hyoung
Abstract: A distributed formation tracking problem considering collision avoidance among robots is investigated for a class of networked mobile robots with unknown slippage effects. The position information of the leader robot is time-varying and accessible to only a small fraction of the follower robots. The skidding and slipping effects are considered in the kinematics and dynamics of multiple mobile robots and assumed to be unknown, together with the matrices of the robot dynamics. A distributed recursive design methodology using the function approximation technique is derived to design each follower robot's local controller with collision avoidance ability under directed networks. The main difficulty of this design is deriving the adaptive compensation laws of unknown slippage effects in order to achieve both formation tracking and collision avoidance by using one local controller for each follower under limited communication links. The boundedness of all signals in the networked closed-loop system and guaranteed collision avoidance among robots are established through Lyapunov stability analysis.